Activated Tumor-infiltrating Fibroblasts Predict Worse Prognosis in Breast Cancer Patients - Hu, Guoming (J Cancer, 2018)
Purpose: Activated tumor-infiltrating fibroblasts were significantly associated with survival of cancer patients. However, they are heterogeneous population, and the prognostic role of these cells in human breast cancer still remains controversial. Herein, we performed the meta-analysis to better understand the role of these cells in prognosis prediction for breast cancer patients. Methods: We searched PubMed and EBSCO to identify the studies evaluating the association of intratumoral activated fibroblast density detected by immunohistochemical (IHC) method and overall survival (OS) and/or disease-free survival (DFS) in breast cancer patients, then computed extracted data into hazard ratios (HRs) for OS, DFS and clinicopathological features such as lymph node metastasis, TNM stage with STATA 12.0. Results: A total of 3680 patients with breast cancer from 15 published studies were incorporated into this meta-analysis. We found that the infiltration of activated fibroblasts significantly decreased overall survival (OS) and disease-free survival (DFS) in patients. In stratified analyses, high density of FSP-1(+) or podoplanin(+) fibroblasts was significantly associated with worse OS; while α-SMA(+) or podoplanin(+) fibroblast infiltration was associated with worse DFS in breast cancer. In addition, elevated number of activated tumor-infiltrating fibroblasts significantly correlated with lymph node metastasis and poor tumor differentiation of patients. Conclusion: The infiltration of activated fibroblasts, especially the FSP-1(+) or podoplanin(+) fibroblasts leads to worse clinical outcome in breast cancer patients, implicating that it is a valuable prognostic biomarker and targeting it may have a potential for effective treatment.